Udmurdi rahva arusaamad kosmogooniast: tähtede nimed ja nende kujutamine rahvaluules - Tatiana Vladykina (Mäetagused)
Cosmogonic concepts of the Udmurt people can be detected through the names of stars, the nomination of which is usually based on mythological cognition. Additional and very significant information about space objects is contained in folklore texts. The images of stars are included in a stable triad of heavenly bodies along with the sun and the moon. Their constant feature is bright light, opposed to images of negative energy, forces of darkness – diseases or sorcerers. Therefore, images of stars are frequently used in conspiracy formulas, where they are presented as an insurmountable barrier to those who do evil. The stars, along with the sun and the moon, become metaphors and comparisons in the song culture of the Udmurt people. They are used as analogies in the characterization of family and kinship ties, testifying to the relationships within the clan. Stars/constellations as a symbol of unattainability and indivisibility are a kind of guarantor of the stability of the world.